Stability analysis of a recombinant bacterium with larvicidal activity - RESTREPO, NORA HELENA; PATIÑO, MARÍA MERCEDES; ORDUZ, SERGIO (Revista Colombiana de Entomología, 1996)
The recombinant DNA technology offers new alternatives in the production of improved microorganisms for large scale production. However, the stability of recombinant plasmids during long culture periods is a serious problem for industrial use. The aim of this work was to introduce in the native aquatic bacterium Bacillus thuringiensis subsp. israeliensis CIB 30-0501b the plasmid pGSP11 that contains the genes coding the binary toxin of B. sphaericus and to analyze the expression and stability of this plasmid under laboratory conditions. This analysis showed that the bacterium grew best in the culture medium Lucia Bertani broth at 28°C with tetracicline (30 mg/mi). The presence of the pGSP11 plasmid was detected after eight hours of growth, coinciding with the moment that the expression of the plasmid-coded toxins started. An increase in the culture temperature was always correlated with a decrease in toxin synthesis which was not accompanied by plasmid loss. The presence of the selection antibiotic showed an important effect on plasmid conservation.